EMPOWERING COASTAL COMMUNITIES THROUGH REVITALIZATION OF THE LEMBUNG MANGROVE ECOTOURISM AREA IN LEMBUNG VILLAGE, GALIS DISTRICT, PAMEKASAN REGENCY - Ach. Muhib Zainuri; Mohamad Sinal; Moh. Hartono; Hari Kurnia Safitri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Mangrove forests play a vital role in protecting coastal areas. They regulate hydrological functions and prevent natural disasters. At the same time, these ecosystems support biodiversity, provide habitat for fish, crustaceans, and birds, and support the livelihoods of local residents. In Lembung Village, Galis District, Pamekasan Regency, community service workers from the State Polytechnic of Malang, along with the “Sabuk Hijau” tourism awareness group, are expanding mangrove revegetation efforts to strengthen their coastline while creating sustainable livelihoods through silvofishery and the introduction of fish processing technology. Silvofishery itself is a system that combines mangrove forest conservation with mangrove crab cultivation, while fish processing technology is introduced to utilize the abundant fish available locally for sale in dried form. The purpose of this community service is to implement mangrove conservation in synergy with silvofishery, thus providing ecological, social, and economic benefits for the local community, preserving natural resources, and strengthening the ecotourism-based economy of coastal communities through the introduction of fish processing technology. The results of this community service include revegetation of one hectare of mangrove forest, construction of a silvofishery area, and a fish drying machine.